Is accurate taxon identification important for molecular studies? Several cases of faux pas in pentatomoid bugs (Hemiptera: Heteroptera: Pentatomoidea) - Lis, Jerzy A.; Lis, Barbara (Zootaxa, 2011)
Recently, DNA has become a major source for phylogenetic inference. Although, in entomology, morphology-based methods of taxon identification and the use of morphological data for phylogenetic analyses remain prevalent, the value of these types of studies (often called “traditional”) are depreciated from time to time. It is obvious, that wrong taxon identification may affect results of any taxonomic study. Here we examine evidence that not only the modern “molecular” taxonomists, but even the so-called “traditional” taxonomists, may be casual and irresponsible in taxa identification, when they do their phylogenomic research. We also argue that a researcher’s responsibility for proper taxon identification and its naming is actually much higher in molecular studies than in any others.